2008
DOI: 10.1590/s0103-64402008000200015
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol granuloma of the maxillary sinus

Abstract: Cholesterol granuloma (CG) is a foreign body reaction to the deposition of cholesterol crystals, usually found in association to chronic middle ear diseases, being highly uncommon in the paranasal sinuses. This article reports a case of CG in the maxillary sinus of a 22-year-old man, manifesting as a swelling on the right maxilla associated with pain and nasal obstruction. Computed tomography (CT) imaging showed complete opacification of the right maxillary sinus with cortical bone expansion and destruction. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Almada et al [10] reported that there are chances of primarily or secondarily inflamed odontogenic lesions that exhibit foreign body reaction to cholesterol crystals in their capsule and could extend to maxillary sinuses due to anatomical continuity. Yamazaki et al [9] reported that CG seems to be one of the driving forces for growth of jaw cysts, especially those with inflammatory background.…”
Section: Discussionmentioning
confidence: 99%
“…Almada et al [10] reported that there are chances of primarily or secondarily inflamed odontogenic lesions that exhibit foreign body reaction to cholesterol crystals in their capsule and could extend to maxillary sinuses due to anatomical continuity. Yamazaki et al [9] reported that CG seems to be one of the driving forces for growth of jaw cysts, especially those with inflammatory background.…”
Section: Discussionmentioning
confidence: 99%
“…6 It can develop in a variety of body areas such as: the middle ear (most common site), mastoid process, testis, lungs, apex of temporal bone pyramid and paranasal sinuses. 7 Unlike cholesterol granuloma, development of ameloblastoma or even squamous cell carcinoma within dentigerous cysts have been previously reported. 8,9 The incidence of cholesterol crystals is reported as highest in inflammatory cysts, particularly in radicular cysts, while the lowest incidence is reported for cysts of non-inflammatory origin such as odontogenic keratocyst.…”
Section: Cholesterol Granulomamentioning
confidence: 99%
“…3 Obstructed drainage and impaired ventilation are considered significant etiological factors. 4 Cholesterol granulomas most commonly develop in the mastoid portion of the temporal bone and middle ear. 5 Here, we report a rare case involving an elderly man with a cholesterol granuloma in the right orbitofrontal region that possibly developed after facial trauma.…”
Section: Introductionmentioning
confidence: 99%